2015
DOI: 10.1002/jcp.24946
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Environmental Disruption of Circadian Rhythm Predisposes Mice to Osteoarthritis‐Like Changes in Knee Joint

Abstract: Circadian rhythm dysfunction is linked to many diseases, yet pathophysiological roles in articular cartilage homeostasis and degenerative joint disease including osteoarthritis (OA) remains to be investigated in vivo. Here, we tested whether environmental or genetic disruption of circadian homeostasis predisposes to OA-like pathological changes. Male mice were examined for circadian locomotor activity upon changes in the light:dark (LD) cycle or genetic disruption of circadian rhythms. Wild-type (WT) mice were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 51 publications
2
61
0
1
Order By: Relevance
“…Although a clock-independent role of BMAL1 cannot be completely ruled out (22,40), our data strongly support the role of BMAL1 in cartilage maintenance through its function as a central modulator of the circadian rhythm in gene expression. These results, together with the OA-like knee damage seen in mice subjected to environmental disruption of circadian rhythms (15), favor a hypothesis that BMAL1-regulated circadian rhythm is critical for cartilage function. Therefore, the cartilage phenotype observed here is likely due to a combined effect of the circadian dysregulation of multiple pathways.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Although a clock-independent role of BMAL1 cannot be completely ruled out (22,40), our data strongly support the role of BMAL1 in cartilage maintenance through its function as a central modulator of the circadian rhythm in gene expression. These results, together with the OA-like knee damage seen in mice subjected to environmental disruption of circadian rhythms (15), favor a hypothesis that BMAL1-regulated circadian rhythm is critical for cartilage function. Therefore, the cartilage phenotype observed here is likely due to a combined effect of the circadian dysregulation of multiple pathways.…”
Section: Discussionmentioning
confidence: 70%
“…Previous work identified autonomous cartilage circadian rhythms in mice that became dysregulated with age and upon chronic inflammation (11)(12)(13)(14). Moreover, environmental disruption of circadian rhythms in mice (mimicking chronic jet lag) predisposes knee cartilage to OA-like damage (15), further supporting the idea of an involvement of circadian rhythm disruption in OA development.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…In stem cells isolated from leptin-deficient mice, the NF-κB activation was down-regulated by the treatment of EPA [195]. In a recent study, increased activation of the protein kinase Cδ (PKCδ)-ERK-RUNX2/NFκB signaling pathways were found to be present in the articular chondrocytes of environmentally shifted mice [196]. Extension of this study compared the effects of high-fat diet (HFD) versus normal diet (ND) on OA development and concluded that HFD increased the activation of the same signaling pathway [197].…”
Section: Literature Reviewmentioning
confidence: 99%